2017
DOI: 10.1210/en.2016-1586
|View full text |Cite
|
Sign up to set email alerts
|

N-Acetylcysteine Prevents Low T3 Syndrome and Attenuates Cardiac Dysfunction in a Male Rat Model of Myocardial Infarction

Abstract: Nonthyroidal illness syndrome (NTIS) affects patients with myocardial infarction (MI). Oxidative stress has been implicated as a causative factor of NTIS, and reversed via N-acetylcysteine (NAC). Male Wistar rats submitted to left anterior coronary artery occlusion received NAC or placebo. Decreases in triiodothyronine (T3) levels were noted in MI-placebo at 10 and 28 days post-MI, but not in MI-NAC. Groups exhibited similar infarct areas whereas MI-NAC exhibited higher ejection fraction than did MI-placebo. L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
26
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(31 citation statements)
references
References 32 publications
5
26
0
Order By: Relevance
“…This is confirmed by the positive correlation of D3 with carbonyls and the negative correlation with TRx (Fig 5). These findings are in line with other studies, that demonstrated increased antioxidant defenses after MI in the presence of antioxidant medication, rebalancing the redox status, preventing changes in thyroid metabolism and improving cardiac function [3].…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…This is confirmed by the positive correlation of D3 with carbonyls and the negative correlation with TRx (Fig 5). These findings are in line with other studies, that demonstrated increased antioxidant defenses after MI in the presence of antioxidant medication, rebalancing the redox status, preventing changes in thyroid metabolism and improving cardiac function [3].…”
Section: Discussionsupporting
confidence: 92%
“…These series of parameters is consistent with that assessed in other studies by our research group [6, 8, 16] and others as well [26, 27]. In addition, the reduction in cardiac function may be largely explained by increased protein oxidation (augmented carbonyl levels) and D3 activity in cardiac tissue sample of the infarcted animals [3]. With regard to hemodynamic parameters, SBP increased regardless of the animals’ status (acute MI or sham) showing that, in this experimental model, acute MI did not induce any hemodynamic changes.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…While T4 is solely a product of the thyroid gland, T3 is a product of the thyroid and of many other tissues. Low T3 level has been proven to be correlated with myocardial damage in animal models [12] and is associated with a poor cardiovascular prognosis in human [11, 13, 14]. Previous studies have indicated that subclinical hypothyroidism could be a predictor of adverse cardiovascular outcomes in patients with acute decompensated heart failure [1416], and low T3 has been correlated with worse hospital outcomes in patients with acute HF [11, 14].…”
Section: Introductionmentioning
confidence: 99%
“…Importantly, DIO3 is reexpressed in normal and pathological hyperproliferative conditions. DIO3 reactivation has been demonstrated in the pathological context of cardiac hypertrophy, myocardial infarction, critical illness and several types of cancer (Huang 2005, Lehnen et al 2017.…”
Section: Introductionmentioning
confidence: 99%